Status Incongruence in Advanced Societies - Dogan, Mattei (SocietàMutamentoPolitica, 2011)
The concept of Status Incongruence is becoming more and more important in Europe and the United States at a time when the old concept of social classes is declining. Today, discrepancies in social status are more relevant in explaining political life than concept of social class. The article proposes a critical assessment of the concept of Status Incongruence in advanced society and an analysis of its configurations.